Bipolar Spectrum Disorders in Male Youth: The Interplay between Symptom Severity, Inflammation, Steroid Secretion, and Body Composition - Walther, Andreas; Penz, Marlene; Ijacic, Daniela; Rice, Timothy R. (Frontiers in Psychiatry, 2017)
The morbidity and societal burden of bipolar spectrum disorders (BSD) in youth are high. These disorders are multi-systemic and in adult populations have clear interactions with inflammatory processes and steroidal physiological systems. There is much less data concerning these areas of study in youth populations with BSD. This is surprising to us given the association of youth-onset BSD with puberty and its associated physiological changes. In this mini-review we overview our knowledge of the role of inflammatory processes and steroidal physiological systems in youth BSD, describing the greater literature in adult populations, detailing the literature in youth populations when available, and overviewing current proposed molecular mechanistic pathways based on the available data. We go on to consider the interaction effects between these two areas of interest. We also attend to the interplay of this complex system with body composition and weight gain, an especially important consideration in relation to the role of second generation antipsychotics as the first line treatment for youth with BSD in major clinical guidelines. A developmental model of early onset BSD for boys is hypothesized with pubertal hormonal changes increasing risk for first (hypo-)manic/depressive episode. The dramatic androgen-rise with high velocity during puberty might be relevant for first onset of BSD in boys. A shift from general hypercortisolism driven by glucocorticoid resistance to hypocortisolism with further disease progression is assumed, while increased levels of inflammation are functionally associated with the endocrine dysregulations. The interacting role of overweight and obesity in youth with BSD further indicates leptin resistance to be a central moderator of the dynamic neurobiology of BSD in youth. The intent of this mini-review is to advance our knowledge of youth BSD as multi-systemic disorders with important contributions from endocrinology and immunology based on a developmental perspective. This knowledge can influence current clinical care and more importantly inform future research.